Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/rs11111319
|View full text |Cite
|
Sign up to set email alerts
|

Downscaling Land Surface Temperature from MODIS Dataset with Random Forest Approach over Alpine Vegetated Areas

Abstract: In this study, we evaluated three different downscaling approaches to enhance spatial resolution of thermal imagery over Alpine vegetated areas. Due to the topographical and land-cover complexity and to the sparse distribution of meteorological stations in the region, the remotely-sensed land surface temperature (LST) at regional scale is of major area of interest for environmental applications. Even though the Moderate Resolution Imaging Spectroradiometer (MODIS) LST fills the gap regarding high temporal reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 67 publications
(112 reference statements)
2
33
0
1
Order By: Relevance
“…These differences in evapotranspiration are consistent with our findings of cooler temperatures in taller forests. Using multispectral sensors, others have found land surface temperature is affect by land cover type and biophysical characteristics, such as elevation and aspect, at moderate to coarse spatial resolutions [91,92]. Our methods were able to detect differences in land surface temperature at moderately high spatial resolution in the same vegetation type, elevation, and aspect, confirming that annual metrics increase the ability of remote sensors to distinguish ecological characteristics in tropical forests.…”
Section: Improving Ch Mappingsupporting
confidence: 75%
“…These differences in evapotranspiration are consistent with our findings of cooler temperatures in taller forests. Using multispectral sensors, others have found land surface temperature is affect by land cover type and biophysical characteristics, such as elevation and aspect, at moderate to coarse spatial resolutions [91,92]. Our methods were able to detect differences in land surface temperature at moderately high spatial resolution in the same vegetation type, elevation, and aspect, confirming that annual metrics increase the ability of remote sensors to distinguish ecological characteristics in tropical forests.…”
Section: Improving Ch Mappingsupporting
confidence: 75%
“…More machine learning (ML) based downscaling approaches were explored to construct a nonlinear regression model which addresses the nonlinear relationship between LST and the land surface parameters. The current LST downscaling methods based on ML algorithms, containing artificial neural networks (ANN), support vector machine (SVM), and random forests (RF), have displayed higher accuracies in tackling the nonlinear relationship between LST and the land surface parameters [30][31][32][33][34]. Hutengs and Vohland [11] applied RF to downscale 1 km MOD11A1 LST 250 m in a complex terrestrial environment of Jordan River Region in the Eastern Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…The basic concept of RF is to construct a set of uncorrelated classification and decision regression trees. RF is capable to unite a big number of binary decision trees constructed using bootstrap samples from the training dataset and randomly select a subset of independent variables and dependent variables at each node [35]. The results of RF training turn out to be the voting output for all decision trees.…”
Section: ) Downscaling Lst Using a Random Forest Modelmentioning
confidence: 99%
“…Compared to common statistics-based downscaling LST methods, RF is more efficient in complex regions, especially in urban areas. Bartkowiak et al [35] evaluated three LST downscaling methods in Alpine vegetated areas, RF was found capable of modelling non-linear relationships between LST and variables in a very robust way. It has been proven that RF can improve LST downscaling performance in arid regions (especially in deserts) [40].…”
Section: ) Downscaling Lst Using a Random Forest Modelmentioning
confidence: 99%